2022
DOI: 10.1093/rap/rkac064
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of a brief fatigue intervention for inflammatory arthritis: a qualitative process evaluation

Abstract: Objectives We developed a brief cognitive-behavioural, one-to-one intervention to reduce fatigue impact for patients with inflammatory arthritis. This qualitative process evaluation explored intervention acceptability and potential refinements from the perspective of (i) patients who attended sessions and (ii) rheumatology health professionals (RHPs) who delivered the intervention. Methods Interviews were conducted with patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This awareness should facilitate discussions with people who have I-RMDs about which specific factors might be pertinent for them as individuals. People with I-RMDs have reported that being asked about their fatigue can be validating and make them feel less isolated; for some, it can be the first step to self-management 38 39…”
Section: Overarching Principlesmentioning
confidence: 99%
“…This awareness should facilitate discussions with people who have I-RMDs about which specific factors might be pertinent for them as individuals. People with I-RMDs have reported that being asked about their fatigue can be validating and make them feel less isolated; for some, it can be the first step to self-management 38 39…”
Section: Overarching Principlesmentioning
confidence: 99%